A Rank-Size Rule Analysis of The City System at The Country and Province Level in Turkey - Seda Kundak; Vedia Dökmeci (Iconarp International Journal of Architecture and Planning, 2018)
The present study investigates the rank-size distribution of cities above 10,000 in Turkey for the years 2000 and 2012, and the results are compared with the findings related to 1945 and 1975.  The results show that despite the political and economic transformations of the last decade, there is a perfect adjustment of the city size distribution to the rank-size rule at the country level due to existence of a well-established urban system. A regression analysis is employed to reveal the relationships between the slopes of city size distribution and the characteristics of provinces.